Conformally and gauge invariant spin-2 field equations - Mayor, C. S O [UNESP]; Otálora, G. [UNESP]; Pereira, J. G. [UNESP] (Pleiades Publishing, 2013)
Using an approach based on the Casimir operators of the de Sitter group, conformally invariant equations for a fundamental spin-2 field are obtained, and their consistency is discussed. It is shown that only when the spin-2 field is interpreted as a 1-form assuming values in the Lie algebra of the translation group, rather than a symmetric second-rank tensor, the field equation is both conformally and gauge invariant. © 2013 Pleiades Publishing, Ltd.